Reduced Fractionation in Lung Cancer Patients Treated with Curative-intent Radiotherapy during the COVID-19 Pandemic. Issue 8 (August 2020) - Faivre-Finn, C.; Fenwick, J.D.; Franks, K.N.; Harrow, S.; Hatton, M.Q.F.; Hiley, C.; McAleese, J.J.; McDonald, F.; O'Hare, J.; Peedell, C.; Pope, T.; Powell, C.; et al.
Abstract: Patients treated with curative-intent lung radiotherapy are in the group at highest risk of severe complications and death from COVID-19. There is therefore an urgent need to reduce the risks associated with multiple hospital visits and their anti-cancer treatment. One recommendation is to consider alternative dose-fractionation schedules or radiotherapy techniques. This would also increase radiotherapy service capacity for operable patients with stage I-III lung cancer, who might be unable to have surgery during the pandemic. Here we identify reduced-fractionation for curative-intent radiotherapy regimes in lung cancer, from a literature search carried out between 20/03/2020 and 30/03/2020 as well as published and unpublished audits of hypofractionated regimes from UK centres. Evidence, practical considerations and limitations are discussed for early-stage NSCLC, stage III NSCLC, early-stage and locally advanced SCLC. We recommend discussion of this guidance document with other specialist lung MDT members to disseminate the potential changes to radiotherapy practices that could be made to reduce pressure on other departments such as thoracic surgery. It is also a crucial part of the consent process to ensure that the risks and benefits of undergoing cancer treatment during the COVID-19 pandemic and the uncertainties surrounding toxicity from reduced fractionation have been adequately discussed with patients. Furthermore, centres should document all deviations from standard protocols, and we urge all colleagues, where possible, to join national/international data collection initiatives (such as COVID-RT Lung) aimed at recording the impact of the COVID-19 pandemic on lung cancer treatment and outcomes.